ANALISIS DISTRIBUSI SPASIAL MARGA CURCUMA DIJAWA - Roemantyo Roemantyo (Research Center for Biology-Indonesian Institute of Sciences, 2000)
Based on the distribution data of 13 species of Curcuma found in Java,spatial analyses using land status and land used thematic maps has been earned out.The purpose of this analysis is to detenvine thehabittat that usually Curcuma grows both cultivated or wild.Cluster analysis based on distance Eucledian using Statistical Program for Social Sciences(SPSS) for Window Release 6 software was administered to classify the relation between Curcuma species and their habitat.The result showed that Curcuma domestica; C. aurantiaca, C. aeruginosa, C. zedoaria, C. xanthorhiza and C.viridifolia are wide distributed in Java, but C. mangga, C. heyneana, C. purpuracens, C. soloensis, C. euchroma, C.colorata and C. borg are strickly found in specific areas only. Eventhough C. phaeocaulis, C. sylvatica and C. ochrorhiza has been reported found in Java, that species should be monitor due to limited information of this species in Java.Spatial analyses using ArcView software showed that Curcuma found in the 13 kinds of land status and land used.Curcuma mainly occupies in the habitat that classify as a